Long-term multicentre randomised controlled study of high frequency chest wall oscillation versus positive expiratory pressure mask in cystic fibrosis. Issue 8 (13th February 2013) - McIlwaine, Maggie Patricia; Alarie, Nancy; Davidson, George F; Lands, Larry C; Ratjen, Felix; Milner, Ruth; Owen, Blythe; Agnew, Jennifer L
Abstract : Background: Positive expiratory pressure (PEP) is the most commonly used method of airway clearance (AC) in Canada for patients with cystic fibrosis (CF) whereas, in some countries, high frequency chest wall oscillation (HFCWO) is the preferred form of AC. There have been no long-term studies comparing the efficacy of HFCWO and PEP in the CF population. Objectives: To determine the long-term efficacy of HFCWO compared with PEP mask therapy in the treatment of CF as measured by the number of pulmonary exacerbations (PEs). Methods: A randomised controlled study was performed in 12 CF centres in Canada. After a 2-month washout period, subjects were randomised to perform either HFCWO or PEP mask therapy for 1 year. Results: 107 subjects were enrolled in the study; 51 were randomised to PEP and 56 to HFCWO. There were 19 dropouts within the study period, of which 16 occurred prior to or at the time of randomisation. There were significant differences between the groups in the mean number of PEs (1.14 for PEP vs 2.0 for HFCWO) and time to first PE (220 days for PEP vs 115 days for HFCWO, p=0.02). There was no significant difference in lung function, health-related quality of life scores or patient satisfaction scores between the two groups. PEP mask therapy required a shorter treatment time. Conclusions: The results of this study favour PEP and do not support the use of HFCWO as the primary form of AC in patients with CF. Clinical Trial Registration number: NCT00817180.